Advanced Photon Source. Issue 2 (3rd March 2016) - Austin, Elizabeth
Abstract : The Advanced Photon Source (APS) at Argonne National Laboratory is preparing for a major upgrade, centered on installation of a multibend achromat (MBA) lattice that will dramatically improve the brightness, coherence, and stability of the X-ray beams.